Evidence for auto-catalytic mineral dissolution from surface-specific vibrational spectroscopy - Jan Schaefer; Ellen H. G. Backus; Mischa Bonn (Nature Communications, 2018)
Although it is well known that silica can dissolve in water, the precise mechanism is unclear. Here, the authors employ sum frequency generation spectroscopy to probe the interfacial water structure reporting directly on the underlying dissolution mechanism, which appears to be auto-catalytic.